2022
DOI: 10.3390/jcdd9110405
|View full text |Cite
|
Sign up to set email alerts
|

New Wound Management of Driveline Infections with Cold Atmospheric Plasma

Abstract: The use of ventricular assist devices as a bridge to transplant or as destination therapy has increased. Wound complications increase morbidity in this cohort. Cold atmospheric plasma is a source of reactive oxygen and nitrogen species and can reduce the microbial load in skin wounds without negative effects on the surrounding tissue. We evaluated our cold atmospheric plasma treatment for LVAD driveline infections in a retrospective single-center study for peri- and postintervention outcome analysis. Between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For more extensive, deep infections, along with standard techniques such as driveline repositioning, vacuum-assisted, and argon plasma therapy. 13 We think that the implementation of these new procedures in the treatment also had an impact on the overall mortality of patients in the second period, although it is an area of persistent challenge with room of further improvement. Infections, and especially driveline infection, remain the biggest burden among adverse events, 10 and only a future change in the driveline connection can reduce the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…For more extensive, deep infections, along with standard techniques such as driveline repositioning, vacuum-assisted, and argon plasma therapy. 13 We think that the implementation of these new procedures in the treatment also had an impact on the overall mortality of patients in the second period, although it is an area of persistent challenge with room of further improvement. Infections, and especially driveline infection, remain the biggest burden among adverse events, 10 and only a future change in the driveline connection can reduce the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 This can decrease the microbial load in skin wounds. 18 Moreover, cold plasma stimulates the growth and proliferation of endothelial cells and activates regenerative processes in the lower strata of the skin. Another effect is that the electrical fields and heat also stimulate microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recent retrospective analysis showed that, in patients with LVAD implants, treatment of already infected drivelines with ACP was associated with a significant DLI reduction. 18 According to a recent calculation, the ACP approach is able to reduce treatment costs of patients with wound infections by about 50%. 12 Our data indicate that ACP also has preventive effects, which can last several months.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular assist devices (LVAD) for patients with terminal heart failure (HF) have become a standard treatment option for patients, however, driveline (DL)-associated infections seriously contribute to morbidity and mortality in this patient cohort and fully implantable system are not available so far. 1,2 Up to 20% of LVAD patients developed driveline infection (DLI) within 1 year after implantation. 3 The MOMENTUM 3 trial revealed an increased mortality rate in the infection group.…”
mentioning
confidence: 99%